Inorganic Composition Modulation of Solid Electrolyte Interphase for Fast Charging Lithium Metal Batteries - Tan, Yi‐Hong; Liu, Zhu; Zheng, Jian‐Hui; Ju, Zhi‐Jin; He, Xiao‐Ya; Hao, Wei; Wu, Ye‐Chao; Xu, Wen‐Shan; Zhang, Hao‐Jie; Li, Guo‐Qing; Zhou, Li‐Sha; Zhou, Fei; et al. (Advanced materials (Weinheim), 2024)
The solid electrolyte interphase (SEI) with lithium fluoride (LiF) is critical to the performance of lithium metal batteries (LMBs) due to its high stability and mechanical properties. However, the low Li ion conductivity of LiF impedes the rapid diffusion of Li ions in the SEI, which leads to localized Li ion oversaturation dendritic deposition and hinders the practical applications of LMBs at high‐current regions (>3 C). To address this issue, a fluorophosphated SEI rich with fast ion‐diffusing inorganic grain boundaries (LiF/Li3P) is introduced. By utilizing a sol electrolyte that contains highly dispersed porous LiF nanoparticles modified with phosphorus‐containing functional groups, a fluorophosphated SEI is constructed and the presence of electrochemically active Li within these fast ion‐diffusing grain boundaries (GBs‐Li) that are non‐nucleated is demonstrated, ensuring the stability of the Li || NCM811 cell for over 1000 cycles at fast‐charging rates of 5 C (11 mA cm−2). Additionally, a practical, long cycling, and intrinsically safe LMB pouch cell with high energy density (400 Wh kg−1) is fabricated. The work reveals how SEI components and structure design can enable fast‐charging LMBs. Lithium fluoride (LiF) can effectively improve the stability of solid electrolyte interphase (SEI). However, the low Li ion conductivity of LiF impedes the rapid diffusion of Li ions in the SEI. To address this issue, a fluorophosphated SEI with fast ion‐diffusing inorganic grain boundaries (LiF/Li3P) is introduced, which enable Li metal batteries to exhibit excellent fast‐charging performance.